Features of the organization of health-improving and recreational motor activity of older women - Galina Putiatina (Kharkiv State Academy of Physical Culture, 2020)
Purpose: to characterize modern approaches and methods of organizing health-improving and recreational motor activity of older women. Material and methods: in this study, a methodological approach was used, according to which the organization of health-improving and recreational motor activity of older women was considered from the point of view of the interaction of different order systems. To achieve this goal, a set of complementary methods was used: analysis of literary sources, documents and Internet resources; analysis of advanced foreign and domestic experience, system analysis method, comparison and contrast method, organizational analysis. Results: it was found that in the composition of the Ukrainian population, the numerical advantage of women over men is observed from the age of 38 and increases with age. In the age group 65 years and older, the number of women is almost 2 times higher than the number of men. The expediency of introducing an experimental approach to increasing the level of health-improving and recreational motor activity of older women by means of health-improving physical culture has been substantiated. Conclusions: as a result of the analysis of the current state of development of the domestic system of health-improving and recreational motor activity, factors have been identified that enhance the role of health-improving motor activity, in particular for older women: the need to inform citizens about the benefits of a healthy lifestyle, regular physical activity; the need to introduce effective mechanisms for the prevention of chronic non-communicable diseases, which have become the main cause of premature mortality; increased negative impact on human health due to a decrease in the volume and intensity of physical activity; a low level of attraction of persons to specially organized physical activity (especially older women), which contradicts the general trends in the development of civilization.